THE IMPLEMENTATION OF VIRTUAL PEER MENTORING IN MICRO TEACHING CLASSES - Tutyandari, Caecilia; Anandari, Christina Lhaksmita; Ardi, Priyatno (LLT Journal: A Journal on Language and Language Teaching, 2022)
This study aims to explore the implementation of virtual peer mentoring in Micro Teaching classes and to identify common teaching aspects assessed by peer observers. Employing an online observation form and focus group discussion, data were collected to address the research questions. The participants were 59 English language education students enrolled in three classes of Micro Teaching. Every student was assigned to do an observation on their peer teacher and give feedback to their performance. At the end of the semester, nine student teachers, representing the three Micro Teaching classes, were invited to a forum group discussion. The current research findings suggest that peer virtual peer mentoring is perceived positively by the participants. Breakout rooms in Zoom platform is a useful tool to give them more personal interactions, especially when sharing the result of observation. Even though giving feedback virtually is a challenge for the student teachers, they appear to see the activity as a valuable process. When observing and commenting on their peer teachers, they also do self-evaluation and reflection. Their peer teaching performance is a way to assess their own performance. Furthermore, other findings reveal common teaching aspects observed, namely linguistic aspects, pedagogical skills, and communication skills.